Synergistic Effects of Acidic pH and Pro-Inflammatory Cytokines IL-1β and TNF-α for Cell-Based Intervertebral Disc Regeneration - BORRELLI, CHIARA (My University, 2020)
The intervertebral disc (IVD) relies mainly on diffusion through the cartilaginous endplates (CEP) to regulate the nutrient and metabolites exchange, thus creating a challenging microenvironment. Degeneration of the IVD is associated with intradiscal acidification and elevated levels of pro-inflammatory cytokines. However, the synergistic impact of these microenvironmental factors for cell-based therapies remains to be elucidated. The aim of this study was to investigate the effects of low pH and physiological levels of interleukin-1ß (IL-1β) and tumour necrosis factor-α (TNF-α) on nasal chondrocytes (NCs) and subsequently compare their matrix forming capacity to nucleus pulposus (NP) cells in acidic and inflamed culture conditions. NCs and NP cells were cultured in low glucose and low oxygen at different pH conditions (pH 7.1, 6.8 and 6.5) and supplemented with physiological levels of IL-1β and TNF-α. Results showed that acidosis played a pivotal role in influencing cell viability and matrix accumulation, while inflammatory cytokine supplementation had a minor impact. This study demonstrates that intradiscal pH is a dominant factor in determining cell viability and subsequent cell function when compared to physiologically relevant inflammatory conditions. Moreover, we found that NCs allowed for improved cell viability and more effective NP-like matrix synthesis compared to NP cells, and therefore may represent an alternative and appropriate cell choice for disc regeneration.
PUBLISHED
Keywords: Nasal chondrocytes; Disc degeneration; Inflammation; Microenvironment; Nucleus pulposus; Cell; Spine; Immunology, Inflammation & Infection; INFLAMMATION